Strategic Transformation: Implementation of an integrated system for efficient management in the equipment & supply chain area - Campos Rojas, Karen Liszeth (2024)
This thesis addresses the critical challenges faced by a leading Peruvian underground mining company specializing in infrastructure and civil works. The research focuses on the issue of equipment downtime, which generates significant financial losses due to poor asset management and a lack of strategic integration, affecting the company's efficiency, competitiveness, and sustainability. The research concludes that this mining contractor company must implement a strategic transformation to improve decision-making and reduce equipment downtime. It is recommended to develop a change management model to adopt new technologies and processes, implement predictive management systems, foster cultural change, and optimize the integration between key areas to promote collaboration and reduce operational inefficiencies. The research provides a comprehensive action framework based on strategic methodology and industry best practices, enabling the company to address its challenges, improve operational efficiency, and ensure long-term sustainability. Adopting a strategic and proactive approach is essential to strengthen the company's competitive position and maximize the value of its assets.